Development of Local Wisdom-Based Worksheets to Improve Science Understanding and Environmental Awareness in Grade IV Students - Pricilia Deyalita Utami; Sunyono Sunyono; Fatkhur Rohman; Muhammad Nurwahidin (Universitas Pendidikan Mandalika, 2026)
Elementary science learning requires contextual materials that help students understand scientific processes and develop environmental responsibility. Preliminary analysis showed that grade IV IPAS worksheets still focused on routine exercises, terminology recognition, and teacher-centered activities, with limited investigation, field observation, and local wisdom integration. This gap makes local wisdom-based worksheets necessary because they connect environmental change concepts with students’ cultural and daily experiences. This study aimed to develop and examine the validity, practicality, and effectiveness of local wisdom-based IPAS worksheets for improving students’ understanding of the nature of science and environmental awareness. The study used a Research and Development design with the 4D model: define, design, develop, and disseminate. The main field trial involved 29 fourth-grade students at SD Xaverius 3 Bandar Lampung. Data were collected using expert validation sheets, teacher and student practicality questionnaires, pretest-posttest tests, and instruments measuring Nature of Science understanding and environmental awareness. The worksheet was highly valid, with an average expert validation score of 97.22%. Practicality reached 96.0% from teachers and 90.8% from students. The overall pretest mean increased from 47.8 to a posttest mean of 85.0, with a mean N-Gain of 0.71 in the high category. The N-Gain reached 76.7% for Nature of Science and 81.5% for environmental awareness. Right-tailed t-tests showed significant results for Nature of Science (t = 6.116, p = 0.000) and environmental awareness (t = 8.938, p = 0.000). The worksheet is valid, practical, and effective for supporting contextual IPAS learning and strengthening scientific literacy and environmental responsibility in elementary schools.